INCIDENCE OF THE INFECTIVE ENDOCARDITIS IN PATIENTS WITH TUNNELED CATHETERS IN ONE BULGARIAN DIALYSIS CENTER PER YEAR - Biser K. Borisov; Konstantin D. Gospodinov; Hristina Y. Hitkova (Peytchinski Publishing, 2022)
Background: Infections are common complications among patients on chronic hemodialysis. Catheter-related bloodstream infections (CRBSIs) are estimated to be 0.15 to 3.5 cases per 1000 catheter-days (CD) in case of tunneled catheters, and the frequency of bacterial endocarditis is estimated at 3.5 to 10% of these. Materials and methods: We retrospectively present data from the study, which was conducted in our clinic for a one-year period from January 1 to December 31, 2018. The average number of patients undergoing hemodialysis was 104, and 33 (32%) of them had tunneled catheters. There was 12 045 total CD. We took chemocultures of all patients with clinical signs dubious about CRBSIs. All patients with positive chemocultures were examined by echocardiography. Results: We have found 19 episodes of CRBSIs in 15 patients (1.5/1000 CD). We found a total of 21 causative microbial agents in positive chemocultures, two of which were polymicrobial. Thirteen of the bacteria (62%) were Gram-positive [G (+)] and eight Gram-negative [G (-)] (38%). The most common G (+) bacterium was Staphylococcus aureus 9 and G (-) - Citrobacter coseri. In six patients (32%) with CRBSIs, we found bacterial endocarditis. Four of them (67%) were infected with G (-) negative agent, and two (33%) - with G (+). Conclusions: We conclude that our high incidence of bacterial endocarditis is probably due to the fact that we have examined all of the patients for this complication and that gram-negative bacteria are more often the cause of bacterial endocarditis in patients undergoing hemodialysis with a tunnel catheter.